Culture and computing : 8th International Conference, C&C 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, proceedings /: 8th International Conference, C&C 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, proceedings. (2020) - Unknown
No abstract available